Peran Guru PPKn Dalam Menumbuhkan Kesadaran Hukum Siswa Kelas VIII di MTs Walisongo 1 Maron - Sitttatil Faizah; Nurul Saila; Ani Sulianti (CV. ITTC INDONESIA, 2024)
Civic teachers play an important role in raising students’ legal awareness at school. The aim of this research is to determine the legal awareness of class VIII students, the role of PPKn teachers, supporting and inhibiting factors as well as solution in raising legal awareness for class VIII students. The research method used is a qualitative with a case study method. The research location chosen was MTs Walisongo 1 Maron. The data sources used are primary and secondary data sources. Data collection techniques include observations, interview, and documentation. Data analysis technique use data reduction, data display and conclusions, while checking the validity of data uses triangulation technique.The research results show that PPKn teachers carried out their roles well. PPKn teachers has taught legal material, reprimands first before giving sanctions, always sets a good example which is imitated by class VIII students. Apart from that, Civics teachers often provide motivation to students about the law and students for maintaining their behavior in obeying the rules and providing sanctions for students who violate them.